Z dokazi podprta medicina / Evidence-based medicine - Vrhovec, Levin (Acta Medico-Biotechnica, 2021)
In the 18th century, the British Royal Navy suffered great losses of personnel. When counting casualties, war analysts discovered that a mysterious disease killed more men than war itself. More than two-thirds of sailors on a average long-distance sail suffered from it, all with the same symptoms: bleeding gums, spots on the thighs, depression, and lack of energy. In 1747, James Lind performed a dietary test in six groups of sick sailors, and divided them by the type of food that they were given. After 6 days, sailors with lemons in their diet, were significantly improving and were almost without any symptoms, whereas the condition of the sailors in all the other groups deterioated. Later studies have linked vitamin C deficiency to a disease called scurvy, and Lind’s experiment was one of the first clinical trials in the history of medicine. About 50 years later on the other side of the Atlantic Ocean, George Washington, the first president of the United States, awoke one day with a severe sore throat after riding a horse on a cold winter night. The best doctors of that time gathered immediately and prescribed their standard treatment. About 3.5 litres of blood was drawn out of Washington’s body in a single day, but he died soon after. Blood-letting was the most common medical practice performed by doctors from antiquity up to the late 19th century, a time span of almost 2,000 years. In 1809, the first randomised clinical trial showed that, if blood-letting were performed in any disease, the chance of a fatal outcome was 10 times higher compared to no therapy at all. Despite that, blood-letting was performed for another 50 years and was gradually abandoned in the late 19th century. Clinical trials have transformed medicine from a dangerous lottery in the 18th century into a rational clinical decision-making process in the modern era. The concept of evidence-based medicine was born. It is defined by the use of the best evidence available for making decisions about individual patients. Traditionally printed textbooks cannot keep up with the exponential growth of medical literature, therefore, online versions have emerged, which allows the addition of the most recent information in real time. Articles in peer-reviewed journals are another essential source for evidencebased clinical practice. There is an enormous number of articles published each day. For instance, Medline lists 157 ophthalmological journals, which on average, publish over 2,000 articles monthly. Therefore, is keeping up to date mission impossible? Almost, but fortunately there are tools that make it plausible. There are many different on-line databases that help us find reliable sources of information. Medline (PubMed) is open for public use and covers the majority of peerreviewed articles. It is the most widely used and represents a gold standard. Sorting out relevant clinical data is another challenge. We need to evaluate the credibility of evidence, as erroneous methodology in a study can lead to irrelevant results. Each study can be rated according to the levels of evidence based on study design. Systematic reviews and meta-analyses of randomised control trials represent the strongest level of evidence, whereas retrospective studies, case series and case reports are rated as a lower level of evidence. The Cochrane Library is an international, nonprofit organisation that prepares, maintains and promotes high-quality systematic reviews . It is maintained by a group of over 28,000 experts who so far have published over 4,000 reviews, which are continuously updated and growing in number. Subject covered ranges from the basic to most challenging clinical decisions; all suported by the best evidence available. In addition to all these tools that help us to practice evidence-based medicine, there are also many others, such as Mendeley, an academic social network and reference manager. Evidence-based practice is a concept of modern medicine that allows us to conduct a rational clinical decision-making process, but it requires an additional effort from a practising physician. We need to remember that it is important to keep asking ourselves on a regular basis: What have I changed recently in my clinical practice and what is the level of evidence supporting it? Levin Vrhovec